Development and application of hyperpolarized krypton-83 as a new MRI contrast agent - Hughes-Riley, Theodore (2014)
Hyperpolarized (hp) gases such 129Xe and 83Kr (spin I = 1/2 and I = 9/2 respectively) can allow for significantly enhanced signal in a number of magnetic resonance applications. As a result there has been a growing interest in recent years to advance hp noble gas technology to non-invasively image the airspace of lungs, with the goal of developing a helpful probe for lung pathologies. 83Kr longitudinal relaxation (T1) has been shown to be sensitive to various surface properties, and may prove to be an interesting for identifying certain diseases including those that change surface chemistry (such as cystic fibrosis) or the surface-to-volume ratio in the lung (like in emphysema).